2007
DOI: 10.1007/s00056-007-0708-z
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the Beighton Hypermobility Index to Determinate the General Joint Laxity Performed by Dentists

Abstract: The Beighton Index is a reliable instrument for dentists when assessing general joint laxity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 25 publications
1
19
1
2
Order By: Relevance
“…Compared to other studies, this discrepancy may also be the result of specificities of the population of northern Germany, where joint hypermobility appears to be relatively prevalent 37 . However, the overall sensitivity of the single items was low (between 0.21 and 0.65).…”
Section: Rheumatologycontrasting
confidence: 79%
“…Compared to other studies, this discrepancy may also be the result of specificities of the population of northern Germany, where joint hypermobility appears to be relatively prevalent 37 . However, the overall sensitivity of the single items was low (between 0.21 and 0.65).…”
Section: Rheumatologycontrasting
confidence: 79%
“…This aspect should be carefully observed in patients with generalized joint hypermobility (GJH), considering that reduction in proprioception can cause hyper-translation of the condyles, generating articular noise and, possibly, internal derangements and joint inflammation (9)(10)(11) . This topic has been addressed in previous studies (7)(8)(9)(10) that reported GJH as a risk factor for the development of TMD signs and symptoms.…”
Section: Discussionmentioning
confidence: 97%
“…Considering the characteristics of GJH, it is suggested that such manifestation affect all articulations, including the temporomandibular joint (TMJ). Several studies report GJH as a risk factor for the development of signs and symptoms of temporomandibular joint dysfunction (TMD) (7)(8)(9)(10) . Due to ligament laxity and, consequently, to impaired proprioception, it is believed that the TMJ be overloaded, resulting in degenerative changes that can be observed in internal derangements and articular inflammation (9)(10)(11) .…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of TMD was carried out using the German version of the RDC/TMD (14), which has been demonstrated to have sufficiently high reliability for the most common TMD diagnoses (15). Reliability, as well as the internal consistency of the hypermobility measurements taken by dentists functioning as examiners, was assessed in a reliability study (16). According to corresponding recommendations (17), intrarater and inter rater reliabilities were found to be very good to excellent (range of intraclass correlation coefficients: 0.84–0.94); Cronbach’s alpha (range: 0.66–0.79) yielded acceptable internal consistency hypermobility measurements (16).…”
Section: Methodsmentioning
confidence: 99%